Kajian Desain Interior Lobby Rumah Sakit Mitra Keluarga di Surabaya - Jirajaya, Tania Kausalya (Intra, 2019)
Along with the development of the era, the types of human needs have also increased. One of them is the human need to get health care. One health institution that provides health care is a hospital. In this study, three Mitra Keluarga hospitals in Surabaya were determined as samples with consideration of being in 3 different locations so that differences could be identified in the three hospitals. The study was conducted to find the typical characteristics and application of ideal standardization of the interior design of hospital lobbies. The theoretical approach used is the theory of interior design according to Francis D. K. Ching. The research method and data analysis used are descriptive qualitative, namely by describing in detail the data obtained from the documentation and direct observation to the location. The results showed that the three research objects had met a hospital's ideal standard both in terms of service and design aspects. Through the existing elements and design principles, the characteristics and atmosphere of space are formed which have affected users’ aesthetic visual comfort.